Redesain Logo UMKM Ken Jaya Food - Ita Purnama; Sulistyo Utami; Tri Wulandari; Nabilla Selvilam Sa’idah; Selfania Selfania (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
UMKM Ken Jaya Food is a business that produces shredded, meatballs and nuggets using tuna as the basic ingredient. Located in Kolo Village which is famous for its abundant tuna fish. This UMKM also helps many local fishermen by buying fishermen's catches. However, this UMKM does not yet have a unique and attractive logo design as a business identity that is easily recognized by consumers. The logo design of UMKM Ken Jaya Food is still a simple logo. Therefore, it is necessary to redesign the logo for UMKM Ken Jaya Food. The method we use is a qualitative method through interviews with business owners and observations of business premises. This research has several stages to go through so that it can produce a visual identity in the form of a logo.